Photodisruption of the Inner Limiting Membrane: Exploring ICG Loaded Nanoparticles as Photosensitizers - Kaat De Clerck; Geraldine Accou; Félix Sauvage; Kevin Braeckmans; Stefaan C. De Smedt; Katrien Remaut; Karen Peynshaert (MDPI AG, 2022)
The inner limiting membrane (ILM) represents a major bottleneck hampering efficient drug delivery to the retina after intravitreal injection. To overcome this barrier, we intend to perforate the ILM by use of a light-based approach which relies on the creation of vapor nanobubbles (VNBs) when irradiating photosensitizers with high intensity laser pulses. Upon collapse of these VNBs, mechanical effects can disrupt biological structures. As a photosensitizer, we explore indocyanine green (ICG) loaded nanoparticles (NPs) specifically designed for our application. In light of this, ICG liposomes and PLGA ICG NPs were characterized in terms of physicochemical properties, ICG incorporation and VNB formation. ICG liposomes were found to encapsulate significantly higher amounts of ICG compared to PLGA ICG NPs which is reflected in their VNB creating capacity. Since only ICG liposomes were able to induce VNB generation, this class of NPs was further investigated on retinal explants. Here, application of ICG liposomes followed by laser treatment resulted in subtle disruption effects at the ILM where zones of fully ablated ILM were alternated by intact regions. As the interaction between the ICG liposomes and ILM might be insufficient, active targeting strategies or other NP designs might improve the concept to a further extent.